2018
DOI: 10.1038/s41598-018-23066-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Xpert MTB/RIF with measures to assess Mycobacterium tuberculosis bacillary burden in high HIV burden areas of Southern Africa

Abstract: Traditionally, smear microscopy has been used as a point-of-care measure of bacillary burden in tuberculosis patients to inform infection control and contact tracing. Xpert MTB/RIF has the potential to replace smear. However, data to support the use of its quantitative output [cycle threshold (CT)] as an alternate point-of-care measure of bacillary burden are limited. This study assessed the correlation (Spearman’s) between CT, smear, culture time-to-positivity (TTP), and clinical factors in patients with Xper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 29 publications
7
27
0
4
Order By: Relevance
“…The former study had a smaller sample size but even with adequate sample size, patient delay which was assessed with time from symptom to diagnosis was found not to be associated with this correlation thus patient delays may have no effect on the correlation of Xpert Ct values with smear or culture [11,17]. Sex was not associated with performance of Xpert Ct values and these findings are similar to what Beynon got and found sex not associated with performance of Ct values [18]. Our findings are further supported by a study by Hanrahan who found sex not to be significantly associated with performance of Ct values even when there was a difference in the mean Xpert Ct values among men and women hence sex has no effect on Xpert Ct values and correlation.…”
Section: Discussionsupporting
confidence: 58%
“…The former study had a smaller sample size but even with adequate sample size, patient delay which was assessed with time from symptom to diagnosis was found not to be associated with this correlation thus patient delays may have no effect on the correlation of Xpert Ct values with smear or culture [11,17]. Sex was not associated with performance of Xpert Ct values and these findings are similar to what Beynon got and found sex not associated with performance of Ct values [18]. Our findings are further supported by a study by Hanrahan who found sex not to be significantly associated with performance of Ct values even when there was a difference in the mean Xpert Ct values among men and women hence sex has no effect on Xpert Ct values and correlation.…”
Section: Discussionsupporting
confidence: 58%
“…The lower sensitivity of Xpert MTB/RIF in individuals with AFB smear‐negative PTB is related to the lower bacillary burden and higher associated C T value compared to individuals with AFB smear‐positive PTB. Individuals with PTB and HIV co‐infection are more likely to have smear‐negative tuberculosis, which implies a lower bacillary burden and higher mean C T values on Xpert testing ( Beynon 2018 ; Lange 2017 ), and this is the likely mechanism for the lower sensitivity of Xpert MTB/RIF for the diagnosis of tuberculosis in people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…At specificity of 70%, CRP identified 90% (28/31) and Xpert-MTB-HR identified 97% (30/31) patients with medium/high Mtb semiquantitative sputum Xpert® MTB/RIF result. Sputum Xpert Ct values and semi-quantitative load have been shown to correlate with sputum smear, 13 which in turn has been shown in multiple studies to predict infectiousness. 26,27 It is thereby conceivable that both of these diagnostics can reliably identify individuals who have high bacillary burden and are more likely to transmit infection.…”
Section: Discussionmentioning
confidence: 97%
“…We examined sensitivity for Xpert MTB/RIF Ct under 28.0, a threshold identified by a recent multi-country study as being 95% sensitive and 54% specific for smear positivity. 13 We selected a sample size of 100 cases and 200 controls to achieve precision in 95% confidence interval of < +/- 6.5% for the expected sensitivity of 90% and specificity of 70%. All analyses were performed using R, and ROC analyses were performed using the pROC package.…”
Section: Methodsmentioning
confidence: 99%